FX Funding Risks and Exchange Rate Volatility-Korea's Case - Ree, Jack (IMF Working Papers; Working Paper ;, 2012)
This paper examines how exchange rate volatility and Korean banks' foreign exchange liquidity mismatches interacted with each other during the Global Financial Crisis, and whether the vulnerability stemming from this interaction has been reduced since then. Structural and cyclical changes after the crisis, including decreasing demand for currency hedges and the diversifying investor base for bonds, point to a possible weakening of the interaction mechanism; and we find evidences are strongly supportive of this.a.